(untitled) (International Research in Economics and Finance, 2022)
Objective: The relationship between neighborhood social and economic features and the residents’ premature mortality rate is a controversial topic that has brought concerns from many local governments. The purpose of this paper was to determine the impacts of three indicators, including numbers of health providers, numbers of drug arrests, and neighborhood equity scores on premature mortality in the 140 neighborhoods in the City of Toronto. Methods: Conducting regression analysis by using the data from January 2018 to December 2018 obtained from OpenData Toronto. The number of health providers, which shows how many medical service sectors the local community has is generated into a dummy variable (<1.5 or ≥1.5 health providers per 1000 people), and all datasets are cleaned into the same unit, which is per thousand people. Both single regressions and multiple regression are used to compare the change in premature mortality rate, which means the deaths occurred before 70 years old. Results: Taking all indicators into weighted consideration, the empirical evidence shows that the premature mortality rate increased by 4% on average with every one additional drug arrest incident occurring per thousand people while with every additional health provider per one thousand citizens, the premature mortality rate will decrease by 10% on average; In terms of neighborhood equity score, one point increase is associated with a roughly 1% decrease in premature mortality rate on average. Conclusion: Social and economic factors are closely associated with the local premature mortality rate and actively improving the local living conditions can decrease the premature mortality rate while preventing serious issues before it actually occurs.